2, 3-Thienoimide-ended oligothiophenes as ambipolar semiconductors for multifunctional single-layer light-emitting transistors. Issue 43 (9th October 2020) - Prosa, Mario; Moschetto, Salvatore; Benvenuti, Emilia; Zambianchi, Massimo; Muccini, Michele; Melucci, Manuela; Toffanin, Stefano
Abstract : In view of developing multifunctional OLETs, 2, 3-thienoimide-ended oligothiophenes are proposed as ideal candidates to effectively ensure good ambipolar field-effect mobility, self-assembly capability and high luminescence in solid state. Abstract : The fascinating combination of light-emitting characteristics and electrical amplification identifies organic light-emitting transistors (OLETs) as key enabling devices for a wide variety of applications, ranging from displays to sensors. Pursuing a dual functionality in a single-layer architecture is the major strength and the major challenge of this technology. Limitations mainly arise from the poor availability of organic semiconductors that are able to ensure good ambipolar behavior in charge transport together with an efficient light-emission in the solid state. In this present study, we report on a new class of thienoimide-ended oligothiophenes as molecular compounds simultaneously endowed with good field-effect mobility for holes and electrons, good processability, self-assembly capability into nanostructures and remarkable properties of photo- and electroluminescence in the solid state. The versatile chemical tuning of the molecular structure and the fine use of both solution-processed and physical deposition techniques in the realization of nanostructured thin-films are the major tools for controlling the packing of molecules and their intermolecular interactions in the solid state. Indeed, the inherent polymorphism of this class of compounds is directly correlated with their electrical and optoelectronic properties as active materials in multifunctional devices. Considering the field-effect transistor as a benchmark device platform, here we propose the extended family of thienoimide-ended oligothiophenes as a case study in virtue of (i) the solid and throughout correlation of the molecular structure and solid-state organization with the figures of merit in transistor-based devices, and (ii) the possibility of engineering highly integrated planar organic optoelectronic devices with multiple functionalities for the investigation of photophysical and charge transport processes in organic compounds and, ultimately, the demonstration of real-setting applications of OLET technology.